Utilizing digital citizenship education to strengthen elementary students' civic skills: a systematic literature review - Arya Chandra Kirana; Fathurrohman; Wuri Wuryandani; David Lailelleru; Ai Haidar Syahmanan; Iftinan R Azzah S (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Digital Citizenship Education (DCE) has emerged as a critical component in developing civic skills among elementary students amid rapid digital transformation. This study aims to examine how DCE is implemented across diverse educational contexts, identify technological, pedagogical, and socio-cultural challenges in its implementation, and explore effective practices that enhance students' digital literacy and civic engagement. Employing a Systematic Literature Review (SLR) with bibliometric analysis guided by the PRISMA framework, this study analyses 66 articles from the Scopus database and further examines them using VOSviewer to map citation networks, international collaboration, and keyword relationships. The findings reveal a significant upward trend in DCE publications since 2021, with the majority of publications originating from Asian and Western countries. DCE is operationalized through digital-based learning, inclusive multimedia approaches, and the integration of cyber wisdom. Key challenges include inadequate technological infrastructure, gaps in teacher competency, and disparities in digital access among social groups. Effective practices encompass digital privacy awareness, cross-subject collaboration, game-based learning, and systemic policy support. This study concludes that effective DCE implementation requires a holistic approach that includes comprehensive policy frameworks, enhanced teacher professional development, and a supportive educational ecosystem to equip elementary students to become ethical and responsible digital citizens.